3S-LEADERSHIP MODEL AS A TOOL OF USING DESIGN THINKING IN THE SYSTEM OF PUBLIC GOVERNANCE - Petrenko, Victor; Dmytro Dzvin; Mark Liutyi; Iryna Ozminska (International Journal of Innovative Technologies in Social Science, 2022)
The problem of integrated implementation of technology and techniques of design thinking, design management and design leadership into public administration should be considered a priority, as this area is the institutional component that determines the level of either innovative development of a society or its stagnation and decline. The dynamic changes in the intellect, mentality, experience, life values and orientations of modern people set new requirements for leaders in the age of intellectual economy, therefore traditional theories and models of leadership no longer meet the needs of group design-thinking. The purpose of this study is to determine a leadership model most adequate to the principles and criteria of design thinking so as to adapt it to the priority use in the processes and procedures of public administration. The tasks of the study are to analyze the expediency of changes in traditional leadership models and tools oriented to new requirements for design leaders; to outline the conditions for the effective management in the “leader-follower” pair in order to substantiate the role of a leader in design-thinking process and identify the leader’s influence on the group’s performance depending on the level of his/her mastery of using design thinking methodology; to assess the level of adequacy of the 3S leadership model to the criteria and methods of design thinking. To reach the objectives of the article the method of comparative analysis was used. The results of the analysis of the known models of design thinking processes revealed that this process is a fundamental condition and basis for leaders to create an atmosphere of effective use of their own intellect and the intellect of their followers in “leader-follower” pair for joint creativity and innovation. The conclusions of the study draw attention to the feasibility of and conditions for integrating the intellect of “leader-follower” pair and using for this purpose a model of 3S-leadership, based on common behavioral phenomena of synarchy, syntelect and synergy of its members. The main condition for the group to use design thinking technology efficiently has been defined as the mastery of design thinking methodology by its leader with the simultaneous use of the 3S-leadership model to influence followers, which will allow all group members to re-orient to the criteria of the 3S-model, their intellectual activity to be organized according to the recommendations of design thinking, and the leader to transform into a real design-leader who ensures a collective synergistic effect, i.e. a joint innovative product. Authors believe that the results of this study will contribute to the development of programs for training design-thinking leaders for the national system of public administration.